1994
DOI: 10.1021/bi00181a018
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Sector of Complex I (NADH:Ubiquinone Oxidoreductase):Subunit Stoichiometry and Substrate-Induced Conformation Changes

Abstract: The electron carriers of the mitochondrial NADH:ubiquinone oxidoreductase (complex I) are contained predominately in two extramembranous subcomplexes, a flavoprotein (FP) and an iron-sulfur protein (IP). FP contains three subunits with molecular masses of 51, 24, and 9 kDa. The 51-kDa subunit carries the NADH binding site and contains FMN and a tetranuclear iron-sulfur cluster. The 24-kDa subunit contains a binuclear iron-sulfur cluster. IP contains seven subunits with molecular masses of 75, 49, 30, 18, 15, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
69
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 38 publications
7
69
0
Order By: Relevance
“…Our observations from cross-linking and limited proteolysis experiments are in agreement with previous studies on bovine complex I, where the number of cross-links between hydrophilic subunits was reduced significantly in the presence of NADH or NADPH, but not NAD ϩ (23). The susceptibility of a number of hydrophilic subunits to tryptic degradation was also increased in the presence of NAD(P)H, but not NAD ϩ (26).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our observations from cross-linking and limited proteolysis experiments are in agreement with previous studies on bovine complex I, where the number of cross-links between hydrophilic subunits was reduced significantly in the presence of NADH or NADPH, but not NAD ϩ (23). The susceptibility of a number of hydrophilic subunits to tryptic degradation was also increased in the presence of NAD(P)H, but not NAD ϩ (26).…”
Section: Discussionsupporting
confidence: 82%
“…In the second model, the catalytic module with electron carriers is distinct from the proton-pumping module. The two modules can be spatially separated; energy transduction takes place through long range conformational changes (4,(21)(22)(23). Sequence comparisons have suggested that subunits NuoL, -M, and -N have evolved from a common ancestor related to K ϩ or Na ϩ /H ϩ antiporters and, thus, are likely to be involved in proton translocation (1,24,25).…”
mentioning
confidence: 99%
“…In more recent models combinations of direct and conformational coupling mechanisms have been suggested to account for the observed pumping stoichimetry of complex I (7,8). In fact, biochemical (28) and structural evidence (29) for redoxlinked conformational changes of complex I has been presented. However, the spatial separation of all redox centers from the membrane domain (3) seems to exclude any direct link between redox chemistry and vectorial proton translocation as defined by Peter Mitchell's "redox-loop" concept (30).…”
Section: Discussionmentioning
confidence: 99%
“…The 18 to 20-kDa polypeptide was the only one that reacted exclusively with NADPH. In earlier publications (Belogrudov and Hatefi 1994;Belogrudov and Hatefi 1996) the investigators mentioned that a 20-kDa subunit was one of the 31 subunits of the hydrophobic-protein (HP) domain that can be obtained by resolution of Complex I with chaotropic agents (Hatefi and Stempel 1967) and that this subunit contained a motif of three Cys residues that could possibly bind a tetranuclear Fe-S cluster. Obviously, this subunit is the PSST subunit.…”
Section: Pyridine-nucleotide Binding Sites In Complex Imentioning
confidence: 99%
“…Obviously, this subunit is the PSST subunit. The iron-sulfur protein (IP) domain of Complex I also contains a 18-kDa subunit (Belogrudov and Hatefi 1994) with AQDQ as the first four residues . This subunit is proposed to modulate the activity of Complex I by way of proteinekinase-A-mediated phosphorylation of a Ser residue by cAMP in its C-terminus (Papa et al 2008).…”
Section: Pyridine-nucleotide Binding Sites In Complex Imentioning
confidence: 99%